PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA PEMBELAJARAN FISIKA KELAS X SMKN 2 PINRAN - Sukriadi; Sixtus Iwan Umboh; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
This research is quasi-experimental research aimed at determining whether Jigsaw's collaborative learning has a positive effect on the learning outcomes of Grade X SMK Negeri 2 PINRANG (on straight motion material) students. The research design was "Pretest-Posttest Control Group Design". The variables in this study are the learning model and the learning outcomes. The independent variable in this study is cooperative jigsaw learning and direct learning, while the dependent variable is student learning outcomes. The population in this study were all grade X SMK NEGERI 2 PINRANG students. The sample in this study consisted of two classes, namely Class X APH1 as the experimental class and Class X APH2 as the control class with the sampling technique by random sampling. There are 12 students in class X APH1 and 12 students in class X APH2 in each class. The results of the analysis show that the mean of the experimental class is 75 and the control class is 42.5 with a standard deviation of 9.29 and 15, respectively. The results of the SPSS analysis using the t-test show that the value of t => is t table = 6.38> 1.717144. Therefore tcount> ttable means that H0 is rejected and H1 is accepted.